2023
DOI: 10.1021/acsnano.3c06687
|View full text |Cite
|
Sign up to set email alerts
|

Strong Replaces Weak: Design of H-Bond Interactions Enables Cryogenic Aqueous Zn Metal Batteries

Changhao Zhu,
Xuye He,
Yun Shi
et al.

Abstract: Despite the numerous advantages of aqueous Zn batteries, their practical application under cryogenic conditions is hindered by the freezing of the electrolyte because the abundance of hydrogen bonds (H-bonds) between H 2 O molecules drives the aqueous system to transform to an orderly frozen structure. Here, a design of H-bond interactions based on the guiding ideology of "strong replaces weak" is proposed. The strong H-bonds formed between introduced eutectic components and water molecules break down the weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…The unshifted absorption peak at 613 cm –1 reflected that SO 4 2– anions still paired with cations, but the larger [NH 4 (H 2 O) m (EG) n − m ] + cations would weaken the Coulombic forces between the anions and cations, which endowed DES-5 with a lower freezing point. The result was consistent with the energy difference between the water–water H-bond (−2.41 kcal mol –1 ) and the water–EG H-bond (−3.83 kcal mol –1 ), which led to the disruption of H-bond networks and the depression of the freezing point in an aqueous system …”
Section: Resultssupporting
confidence: 84%
“…The unshifted absorption peak at 613 cm –1 reflected that SO 4 2– anions still paired with cations, but the larger [NH 4 (H 2 O) m (EG) n − m ] + cations would weaken the Coulombic forces between the anions and cations, which endowed DES-5 with a lower freezing point. The result was consistent with the energy difference between the water–water H-bond (−2.41 kcal mol –1 ) and the water–EG H-bond (−3.83 kcal mol –1 ), which led to the disruption of H-bond networks and the depression of the freezing point in an aqueous system …”
Section: Resultssupporting
confidence: 84%
“…This indicated that the stability of water molecule clusters increased and the proportion of free water decreased. [17,19] These results suggested that the addition of N-ac contributed to the reduction of water molecules within the Zn-ions solvation sheaths as well as the free water in the electrolyte, thus inhibiting the various water-related side-reactions, HER and Zn-metal corrosion. In addition, Fourier…”
Section: Resultsmentioning
confidence: 98%